Extrahepatic and extrapulmonary hydatid cysts as primary lesions - V. Patel, Hepi; P. Vasavada, Dharmesh (International Surgery Journal, 2024)
Background: Hydatid cyst disease, caused by the larval stage of the parasite Echinococcus granulosus, commonly affects the liver and lungs but can also manifest in various extrahepatic and extrapulmonary locations. Splenic hydatid disease, despite being rare, is the third most common location. This paper presents a case series highlighting the clinical presentation, diagnostic challenges, and management strategies for patients with extrahepatic and extrapulmonary hydatid cysts. Several studies already postulated on sites of hydatid cysts which have statistically significant results. Methods: Patients who were operated on for hydatid disease or cystic lesions, which were later diagnosed as hydatid disease, between September 2022-August 2023 were retrieved retrospectively. Patients with lesions localized outside the liver and the lung as well as in liver and lung were enrolled in the study. Fifty-Two patients with extra-hepatic primary hydatid disease were treated surgically at our clinic. The cysts were located in different part of body. Results has undergone statistical methods like Z-test and Mann-Whitney U test. Any patient of any gender admitted with diagnosis of hydatid cyst in any part of body with age >18 but less than 70 years irrespective of any comorbidities. Results: Surgical techniques like partial or total cystectomy with or without tube drainage are good option for management of extrahepatic and extrapulmonary primary hydatid cysts. There were no complications or mortality in the postoperative period. Hydatid cyst is considered in the differential diagnosis of cystic lesions, especially in endemic areas. Surgical technique planned according to the location of the cyst. Conclusions: Cystectomy is a surgical option in extrahepatic and extrapulmonary hydatid cyst which is evaluate better in this study.